Prospek Sistem Perjanjian Kerja Outsurcing Setelah Keluarnya Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Suhartoyo Suhartoyo (Administrative Law and Governance Journal, 2022)
Abstract: This study aims to find out how the prospects for the position of the outsourcing system for workers/labourers are in the current implementation of industrial relations, especially with the enactment of Law no.11 of 2020 concerning Job Creation. This research is a legal research research with a normative law approach which is analyzed using qualitative analysis. The results show that the outsourcing system in the implementation of employment law in the future after the issuance of Law No. 11 of 2020, the outsourcing system is still used because with all its contradictions it is still needed in responding to the dynamics of industrial relations taking place now and in the future, especially with the Covid 19 pandemic which has devastated the world economy, including the Indonesian economy. In order to continue to provide protection for outsourced workers/laborers, the Company or employer no longer relies on the provisions of Law Number 13 of 2003 because the provisions of Law Number 13 of 2003 in particular articles 64 and 65 have been removed and article 66 which has been amended in Law number: 11 of 2020 concerning Job Creation.Keywords: Outsourcing System, Workers/Labourers, Law Number: 11 of 2020. Abstrak: Penelitian ini bertujuan mengetahui bagaimana prospek kedudukan  Sistem 0utsourcing bagi Pekerja/Buruh dalam pelaksanaan hubungan industrial saat ini , apalagi dengan disahkannya Undang-Undang no.11 tahun 2020 tentang Cipta Kerja. Penelitian ini merupakan penelitian Ilmu Hukum dengan pendekatan Hukum Normatif yang dianalisis menggunakan analisis kualitatif.. Hasil  Penelitian menunjukkan bahwa sistem Outsorcing dalam pelaksanaan Hukum ketenagakerjaan ke depan setelah keluarnya undang-Undang nomor. 11 tahun 2020, sistem Outsorcing   tetap dipakai karena dengan segala kontradiksinya ternyata masih diperlukan dalam menjawab dinamika hubungan industrial berlangsung saat ini dan di masa mendatang  apalagi dengan adanya masa pendemi Covid 19 yang telah memporakporandakan perekonomian dunia termasuk juga perekonomian Indonesia. Guna tetap memberikan perlindungan  terhadap pekerja/buruh outsourcing  maka Perusahaan atau pemberi kerja tidak lagi  mendasarkan pada ketentuan   Undang-Undang Nomor 13 Tahun 2003 karena ketentuan dalam Undang-Undang Nomor 13 Tahun 2003 khsusnya pasal 64 dan 65 telah dihapus dan sedangkan pasal 66 yang diubah dalam Undang-Undang nomor : 11 tahun 2020 tentang Cipta Kerja.Kata Kunci : Sistem Outsourcing, Pekerja/Buruh, UU  Nomor : 11 tahun 2020.